Comparision of Clinical and Demographic Parameters of Bacterial and Viral Meningitis among Children (Bangladesh Journal of Medical Microbiology, 2023)
Background: Bacterial meningitis is an emergency condition that need rapid detection. Objective: The purpose of the present study was to compare of clinical and demographics parameters of bacterial and viral meningitis among children. Methodology: This cross sectional study was carried out in the Department of Microbiology at Mymensingh Medical College, Mymensingh, Bangladesh from July 2010 to January 2012 for around 2 years. Clinically suspected patients with meningitis from paediatrics wards of Mymengh Medical College & Hospital (MMCH), Mymensingh, Bangladesh were included in this study. Based on cytological tests and biochemical tests of CSF the study subjects were categorized as bacterial meningitis. Results: A total 115 clinically and laboratory confirmed meningitis patients were enrolled in this study. In this study, most of the cases of study population were in the age group 1 month to 5 years 97(84.3%) cases. Among 35 cases of bacterial meningitis male was predominant than female which was 23(62.8%) cases and 12(37.2%) cases respectively (p=0.05). The clinical findings of meningitis where all of the study population (115) were suffering from fever (100.0%) followed by nausea or vomiting (60.8%) and convulsion (64.3%). Conclusion: In conclusion statistically significantly different is found in the age group, gender and clinical features among the bacterial and viral meningitis patients. Bangladesh Journal of Medical Microbiology, July 2023;17(2):50-54